Transforming educational leadership in higher education with innovative administrative strategies - Kofi Nkonkonya Mpuangnan; Zukiswa Roboji (International Journal of Educational Management and Development Studies, 2024)
In developing nations particularly in Africa, innovative administrative strategies are essential for educational leaders to navigate inherent challenges in education. This study aims to explore how educational leaders in higher education can be equipped with innovative administrative strategies to cause a positive change in education delivery. A systematic literature review was conducted to achieve this aim, drawing on the transformational leadership model as its theoretical underpinning. The search encompassed scholarly publications from major repositories like Scopus, Web of Science, and International Bibliography of the Social Sciences and Textbooks from 1967 to 2023. The search process went a series of exclusive and inclusive processes and yielded 43 research articles. The synthesized findings were analyzed using a thematic approach. The findings indicate that transformational leadership has the potential to incorporate innovation into higher educational administrative practices. It was also found that innovative administrative practices in higher education can be achieved through staff motivation, technology integration, adoption of agile methodologies, collaborative research, interdisciplinary collaboration, seminars, workshops, and positive organizational culture. Based on the findings, professional development programs for managers and administrators in higher education were highly recommended. These programs would help enhance the knowledge and skills of employees in educational administration.